Adaptive alterations in shoulder range of motion and strength in young tennis players - Gillet, B.; Begon, M.; Sevrez, V.; Berger-Vachon, C.; Rogowski, I. (Journal of Athletic Training, 2017)
Context: Playing tennis requires unilateral and intensive movement of the upper limb, which may lead to functional adaptations of the shoulder and an increased injury risk. Identifying which athletes will be future elite tennis players starts at 5 to 6 years of age. Therefore, highly skilled players practice intensively in their childhood. However, whether these functional changes occur during the prepubertal years has not been established. Objectives: To assess changes in glenohumeral-joint-rotation range of motion and strength of the shoulder-complex muscles in prepubertal elite tennis players. Design: Cross-sectional study. Setting: Tennis training sports facilities. Patients or Other Participants: Sixty-seven male tennis players (age range = 7-13 years) selected by a regional tennis center of excellence were divided into 3 biological age groups relative to their predicted age at peak height velocity: greater than 4 (n = 26; age = 8.7 ± 0.7 years, height = 132.4 ± 12.9 cm, mass = 27.8 ± 3.8 kg), 3 to 4 (n = 21; age = 10.3 ± 0.6 years, height = 144.9 ± 5.7 cm, mass = 34.7 ± 4.0 kg), and 2 (n = 20; age = 12.8 ± 1.4 years, height = 158.5 ± 8.7 cm, mass = 43.0 ± 8.2 kg) years before their age at peak height velocity. Main Outcome Measures(s): We measured the internal- and external-rotation ranges of motion of the glenohumeral joint using a goniometer and calculated the total arc of motion. Maximal isometric strength of 8 shoulder muscles was measured using a handheld dynamometer. Strength values were normalized to body weight and used to calculate 4 agonist-to-antagonist strength ratios. Results: The total arc of motion of the glenohumeral joint decreased gradually with biological age (P = .01) due to the decrease in internal-rotation range of motion (P < .001). Absolute strength increased gradually with biological age (P < .001), but the relative strengths and ratios remained similar. Conclusions: Functional adaptations of the shoulder seen in adolescent and adult tennis players were observed in healthy prepubertal players. This knowledge could help clinicians and coaches more effectively monitor shoulder adaptations to tennis practice during the prepubertal years.